1988
DOI: 10.1093/jac/21.4.413
|View full text |Cite
|
Sign up to set email alerts
|

Serogroup specificity and antimicrobial susceptibilities of Neisseria gonorrhoeae isolated in Mexico City

Abstract: The serogroup pattern of 87 clinical isolates of Neisseria gonorrhoeae was determined by monoclonal coagglutination and the in-vitro activity of seven antimicrobial agents against the same strains was tested by an agar dilution method. The frequency of resistance to spectinomycin, ampicillin, penicillin, erythromycin, chloramphenicol and tetracycline was 14.9%, 33.3%, 34.4%, 30%, 40.2% and 41.3%, respectively. All strains were susceptible to cefotaxime. Out of 87 strains tested, 29.8% produced beta-lactamases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…reported that up to 26.3% of gonorrhea isolates from 148 patients were penicillinase producers and up to 4.7% had chromosome-mediated resistance. 48 Similarly, Conde-Glez et al 49 report gonorrhea strains resistant to spectinomycin, ampicillin, penicillin, erythromycin, chloramphenicol, and tetracyclines in frequencies from 9 to 41.3%; however, they do not identify strains resistant to cephalosporins (cefotaxime). 49 The most recent Mexican study was conducted by Escobedo Guerra et al in 2018, which found that up to 10.39% of 60 samples positive for N. Gonorrhoeae had a mutation for reduced susceptibility to antibiotics in the mtrR gene promoting the region of the mtrCDE locus.…”
Section: In México…mentioning
confidence: 99%
See 1 more Smart Citation
“…reported that up to 26.3% of gonorrhea isolates from 148 patients were penicillinase producers and up to 4.7% had chromosome-mediated resistance. 48 Similarly, Conde-Glez et al 49 report gonorrhea strains resistant to spectinomycin, ampicillin, penicillin, erythromycin, chloramphenicol, and tetracyclines in frequencies from 9 to 41.3%; however, they do not identify strains resistant to cephalosporins (cefotaxime). 49 The most recent Mexican study was conducted by Escobedo Guerra et al in 2018, which found that up to 10.39% of 60 samples positive for N. Gonorrhoeae had a mutation for reduced susceptibility to antibiotics in the mtrR gene promoting the region of the mtrCDE locus.…”
Section: In México…mentioning
confidence: 99%
“…48 Similarly, Conde-Glez et al 49 report gonorrhea strains resistant to spectinomycin, ampicillin, penicillin, erythromycin, chloramphenicol, and tetracyclines in frequencies from 9 to 41.3%; however, they do not identify strains resistant to cephalosporins (cefotaxime). 49 The most recent Mexican study was conducted by Escobedo Guerra et al in 2018, which found that up to 10.39% of 60 samples positive for N. Gonorrhoeae had a mutation for reduced susceptibility to antibiotics in the mtrR gene promoting the region of the mtrCDE locus. 50 However, this study did not perform resistance testing with the different antibiotics to confirm or disprove resistance in the bacteria.…”
Section: In México…mentioning
confidence: 99%